Finding the design collapse capacity of a multi-story RC frame in near-fault based on the collapse risk by using the ratio method - Homa Shanehsazzadeh; Mohsen Tehranizadeh; Leila Haj Najafi (Numerical Methods in Civil Engineering)
The collapse risk role has increasingly drawn engineers’ attention in the performance-based design field and engineers tend to design the structures in a way to be qualified enough to resist earthquakes, especially at near-fault sites. Due to specific characteristics of near-fault records, structures in near-fault required more collapse capacity in comparison with far-fault sites. Furthermore, it is necessary to determine the collapse capacity that structures should be designed to comply with standards and to meet the collapse risk limit in the given site. In this research, the ratio method is presented to determine the design collapse capacity of structures based on the risk value of 1% in 50 years as well as the site hazard stemming from the integration scenario for near-fault. In this method, the structure behavior and fundamental period are incorporated, and effect of pulse period is considered as well. This method utilizes the ratio of the collapse capacity of the structure in near-fault to that of far-fault named γ. Consequently, efficient procedures based on nonlinear static pushover are used for obtaining the collapse capacity in far-fault and near-fault. Then, the ratio method is employed on a mid-rise RC frame and the design collapse capacities are acquired for two amounts of Tp/T. The result shows ratio method can be used for any Tp/T values especially those corresponding to the governing Tp at site. Moreover, the least value of γ can be used conservatively since the design collapse capacity of the structure in near-fault is raised by reducing γ.